Multi-environmental investigations of food-feed trait relationships in kharif and Rabi sorghum (Sorghum bicolor (L) Moench) over several years of cultivars testing in India - Blümmel, Michael; Vishala, A.; Ravi, D.; Prasad, Kodukula V.S.V.; Ramakrishna Reddy, C.; Seetharama, N. (2010)
New sorghum cultivars submitted for cultivars testing and release to the All India Coordinated Sorghum Improvement Project (AICSIP), Directorate of Sorghum Research (DSR), Hyderabad, India from 2002 to 2006 were analyzed for food-feed traits at the laboratory of the International Livestock Research Institute (ILRI) in a collaborative DSR-ILRI project. Significant variations were found among genotypes for stover protein and in vitro digestibility. While weak trade-offs between stover fodder quality traits and grain and stover yields were occasionally observed cultivar are available that offer superior grain yield and stover yield and stover fodder quality in both Kharif (rainy season) and Rabi (postrainy) seasons. In Kharif, the high grain yielders’ (>6 tha−1) stover protein content could vary from c. 3.5 to 9% and stover in vitro digestibility from c. 40 to 50%. In high grain yielding (>4 tha−1) Rabi cultivars stover protein content varied from c. 1.5 to 5.5% and stover in vitro digestibility from c. 42 to 55%. Similar relationships were observed between stover protein and in vitro digestibility and stover yields in both the seasons.